2013
DOI: 10.1111/1574-6941.12162
|View full text |Cite
|
Sign up to set email alerts
|

A newly isolatedChlorellasp. from desert sand crusts exhibits a unique resistance to excess light intensity

Abstract: We recently isolated a small green alga from a biological sand crust (BSC) in the NW Negev, Israel. Based on its 18S rRNA and rbcL genes, it is a close relative of Chlorella sorokiniana and of certain strains of C. vulgaris and C. variabilis, but differs substantially in many aspects from C. sorokiniana. Because the classification of Chlorellales is still not resolved, we designated this species as C. ohadii (Trebouxiophyceae) in honor of Professor Itzhak Ohad. Under controlled laboratory conditions, C. ohadii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 67 publications
0
58
0
Order By: Relevance
“…For example the cyanobacterium Microcoleus up-regulates light energy quenching mechanisms, allowing it to continue to photosynthesise at very high light without photoinhibition (Ohad et al, 2010). Among eukaryotes, a newly described Chlorella species, C. ohadii, is well adapted to the harsh conditions of the BSCs and thrives at extremely high light (Treves et al, 2013) . Organisms from environments such as BSCs may thus be ideal candidates for biotechnological exploitation as well as potentially acting as a source of genes to improve the performance of nonextremophiles under stress conditions.…”
Section: Tolerance To High Levels Of Solar Radiationmentioning
confidence: 99%
“…For example the cyanobacterium Microcoleus up-regulates light energy quenching mechanisms, allowing it to continue to photosynthesise at very high light without photoinhibition (Ohad et al, 2010). Among eukaryotes, a newly described Chlorella species, C. ohadii, is well adapted to the harsh conditions of the BSCs and thrives at extremely high light (Treves et al, 2013) . Organisms from environments such as BSCs may thus be ideal candidates for biotechnological exploitation as well as potentially acting as a source of genes to improve the performance of nonextremophiles under stress conditions.…”
Section: Tolerance To High Levels Of Solar Radiationmentioning
confidence: 99%
“…Changes in the preferred electron transfer routes within PSII might also have dramatic effects on the fluorescence yield. An interesting case of almost total uncoupling of fluorescence‐based estimates of PSII activity and oxygen evolution in microalgae is Chlorella ohadii , a green alga isolated from desert crust of Israel (Treves et al ). The uncoupling of the two parameters in C. ohadii was assigned to the proposed cyclic electron flow pathway within PSII (Treves et al , Ananyev et al ), a pathway suggested to participate in photoprotection in excess light also in the diatom P. tricornutum (Feikema et al ).…”
Section: Discussionmentioning
confidence: 99%
“…F51, F2 and F18High temperature (45 °C)High lipid content and lutein production(Pan et al 2011; Xie et al 2013) Chlorella kessleri and Scenedesmus obliquus High temperature (50 °C) and CO 2 level (18%)(de Morais and Costa 2007) Chlorella sp. T-1, K35 and ZY-1High temperature (40 °C) and CO 2 level (70–100%)(Hanagata et al 1992; Maeda et al 1995; Yue and Chen 2005) Dunaliella salina, bardawil , and tertiolecta High salinity (35%) and light intensityb-carotene production(Borowitzka and Siva 2007; Hosseini Tafreshi and Shariati 2009) Chlorella ohadii High light intensity (3500 µE m −2  s −1 )(Treves et al 2013) …”
Section: Photosynthetic Hydrogen Productionmentioning
confidence: 99%